Ultrasonographic Studies of Follicular Activities in Clomiphene Citrate Treated Anoestrus Cows - Patil, Manjusha; lngawale, M.V.; Birade, H.S.; Anwar, A. Syed (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
An experiment on ultrasonographic studies of follicular activities in clomiphene citrate treated anoestrus cows was conducted. Ultrasound scanning was performed to record the follicular activities on alternate day throughout one estrous cycle for control group and from drug administration to induction of estrus in treatment group. The postpartum induced estrus (treatment group) and regular estrus (control group) differed highly significantly (p<0.01) with respect to number of follicles involved in ovulatory wave (6.67 ± 0.21 Vs 5.00 ± 0.45) and significantly (p<0.05) with respect to growth rate (1.82 ± 0.34 Vs 1.04 ± 0.94 mm/day) and increase in diameter of dominant follicle (7.58 ± 0.72 Vs 10.2 ± 0.47 mm). Maximum diameter of ovulatory follicle in induced estrus was greater than regular estrus (16.12 ± 0.56 Vs15.18 ± 0.47 mm), however, it differed non-significantly.